1993
DOI: 10.1002/cyto.990140302
|View full text |Cite
|
Sign up to set email alerts
|

Method for counting mitoses by image processing in feulgen stained breast cancer sections

Abstract: This study describes an image processing method for the assessment of the mitotic count in Feulgen-stained breast cancer sections. The segmentation procedure was optimized to eliminate 9698% of the nonmitoses, whereas 11% of the mitoses did not survive the segmentation procedure. Contour features and optical density measurements of the remaining objects were computed to allow for classification. Twelve specimens were analyzed, nine used to serve as a training set, and three put aside for later use as independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The images were linearly corrected for shading with two empty images, one illuminated and one dark current image. 43 The corrected grey values thus provided a measure for the local optical density.…”
Section: Image Processingmentioning
confidence: 99%
“…The images were linearly corrected for shading with two empty images, one illuminated and one dark current image. 43 The corrected grey values thus provided a measure for the local optical density.…”
Section: Image Processingmentioning
confidence: 99%
“…Earliest attempts in mitotic cell counting were done by Kate et al [4] and Belien et al [5]. Kate et al have reported In the opinion of the authors of this paper, accuracy cannot be cosidered an apt performance measure as the classification of all the cells as non-mitotic alone will give an accuracy of above 90%.…”
Section: Introductionmentioning
confidence: 92%
“…In spite of great advances in histopathological image analysis by professional pathologists, there are many researches and studies for the establishment of computer-aided diagnosis (CAD) utilities to avoid dispersion in inter- and intra-pathological observations. [678910111213]…”
Section: Introductionmentioning
confidence: 99%